Nursing Interventions in the Management of Non-Pulmonary Tuberculosis: A Multidisciplinary Approach with Laboratory Support - Alshahrani, Fahad Abdullah; Al Asmri, Ali Mansour Ali; Saggaf , Faten Alawi; Al Rowaili , Abrar Mansoor; Alsewed, Rania Mohammed; Yousif, Tahani Yousif; Alarad, Reem Sulaiman Atallah; Alsharari, Shaya Mughthi Salman; Alhesi, Neda Eissa; Alseghyer, Abdullah Mohammed; Al-Qahtani, Muhammad Ali Ayed (Journal of Ecohumanism, 2024)
Background: Particularly in immunocompromised people, non-tuberculous mycobacteria (NTM) are a wide collection of mycobacterial species that create major health hazards and are progressively identified as sources of different illnesses. Diagnostic complexity and therapeutic challenges make effective management of NTM infections still tough. Methods: The present study methodically reviews the body of knowledge on nursing interventions used in NTM infection management. It emphasizes the interdisciplinary approach including laboratory support for diagnosis and therapy. Comprehensive database searches revealed pertinent research that underlined the importance of nursing in patient education, symptom management, and collaborative care. Results: The study emphasizes how early detection and therapy of NTM infections depend much on nursing actions. Important conclusions include the need for comprehensive patient evaluations involving examination of clinical symptoms, laboratory monitoring, and the use of customized teaching programs. Optimizing treatment plans and enhancing patient outcomes depend on efficient communication among healthcare professionals including nurses, chemists, and doctors. Conclusion: The management of NTM infections is significantly improved by the incorporation of nursing interventions within a multidisciplinary framework. Nurses greatly help to enhance clinical results and quality of life for patients impacted by NTM by offering thorough treatment addressing both psychological and physical elements of patient health. To improve patient care even further, future studies should concentrate on creating uniform guidelines for nurse activities in NTM treatment.